A New Column in P.Lond. I 121 (Pap.Graec.Mag. VII): Edition and Interpretation. Issue 1 (1st January 2018) - Martín Hernández, Raquel
Abstract : While re-editing Pap.Graec.Mag. VII, I studied ink remains that correspond to the beginning of a column written on the verso of the papyrus that runs in the opposite direction to the rest of the text. The textual remains on these fragments were only transcribed by Wessely in 1893 and there have been no further attempts at editing them. In the present article, I offer a new edition of the text and its identification, as well as a palaeographical study aimed at identifying the scribe and a discussion of the new column's possible function in the context of the magical formulary.